Effectiveness Yoga to Improve The Quality of Sleep in Pregnant Women with Nausea and Vomiting - Setiawati, Nina; Latifah, Lutfiatul; Kartikasari, Aprilia (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
More than half of pregnant women that feel discomfort because of nausea and vomiting pregnancy (NVP)report have been disturbed sleep during pregnancy. Insufficient sleep duration and poor sleep qualityduring pregnancy may increase the risk of adverse pregnancy outcomes, including growth restriction of thefetus, and postpartum depression. Yoga is commonly used for relaxation and is proven effective to reducestress and anxiety in pregnant women so that it is possible to improve the quality of sleep for pregnantwomen. One form of yoga practice in pregnant women is pranayama and restorative yoga postures.Sothisstudy aims to find out whether pranayama and restorative yoga postures effective to improve the quality ofsleep in pregnant women. This quasy experimental study with a control group was conducted on 58pregnant women with nausea and vomiting obtained by purposive sampling method. Respondents weredivided into two groups, 29 respondents in each group. The pranayama and restorative yoga postures weregiven in the intervention group in 30 minutes for 7 days continuously. The quality of sleep was measured bythe Pittsburgh Sleep Quality Index (PSQI). The results of data analysis using the Chi-Square test showedthat there were no differences in sleep quality scores of pregnant women before and after being givenpranayama and restorative yoga postures (p>0.05). Pregnant women with second and third trimester whoexperience nausea and vomiting in this study do not seem to be at increased sleep quality after doingpranayama and restorative yoga postures.Frequency